IMPLIKASI KEWAJIBAN LAPORAN KEUANGAN PADA PERSEROAN PERORANGAN - Sanea, Madelin; Purwanti, Evi; Ismawartati, Ismawartati (Tanjungpura Acta Borneo Jurnal, 2023)
Abstract  To improve economic conditions which are categorized as still low, the government as the holder of the regulatory function opens opportunities for micro and small business actors to establish businesses which are realized through simplification of business establishment registration and capital exemption by adopting the World Bank program, namely EODB (Ease of Doing Business) as an indicator. ease of doing business in a country. The application of EoDB contained in Article 109 of the Job Creation Law Number 11 of 2020 affects Law Number 40 of 2007 concerning Limited Liability Companies which through this rule is recognized as a legal entity, namely an Individual Company based on Government Regulation Number 8 of 2021 concerning Capital Company's Foundation and Registration of Establishment, Amendment, and Dissolution of Companies that Meet the Criteria for Micro and Small Businesses. This study examines the implications of financial statement obligations on individual companies, from the perspective of EoDB or the ease of doing business index adopted by Indonesia from the World Bank. This study uses a normative juridical approach, which consists of primary and secondary legal materials. The research method used in the preparation of this thesis is a normative juridical legal research method. The form of research used by the author is analytical perspective research. The technique used in collecting data is a literature study and the data analysis technique used by the author in this paper is qualitative analysis. The result of this research is that the implication of this financial statement obligation gives a burden to the community in carrying out micro and small businesses. First, the obligation of financial statements that are contrary to the perspective of EODB, secondly, the obligation of Financial Statements cannot support Micro and Small Businesses, and thirdly, the existence of Financial Reporting Obligations in Individual Companies causes difficulties for the community in carrying out Micro and Small businesses. administrative in the form of: a. written warning; b. cessation of Iraq's access to services; or c. revocation of legal entity status.AbstrakUntuk memperbaiki kondisi perekonomian yang dikategorikan masih rendah, pemerintah selaku pemegang fungsi regulator membuka peluang bagi pelaku usaha mikro dan kecil untuk mendirikan usaha yang direalisasikan melalui penyederhanaan pendaftaran pendirian usaha dan pembebasan modal dengan mengadopsi program Bank Dunia yaitu EODB (Ease of Doing Bussiness) sebagai indikator kemudahan berbisnis dalam suatu negara. Penerapan EoDB yang terdapat pada Pasal 109 Undang-Undang Cipta Kerja Nomor 11 Tahun 2020 mempengaruhi Undang-Undang Nomor 40 Tahun 2007 tentang Perseroan Terbatas yang mana melalui aturan ini diakui suatu badan hukum yaitu Perseroan Perseorangan yang didasari oleh Peraturan Pemerintah Nomor 8 Tahun 2021 tentang Modal Dasar Perseroan Serta Pendaftaran Pendirian, Perubahan, dan Pembubaran Perseroan yang Memenuhi Kriteria Untuk Usaha Mikro dan Kecil. Penelitian ini mengkaji tentang Implikasi kewajiban laporan keuangan pada Perseroan Perorangan, dalam prespektif EoDB atau Indeks kemudahan berusaha yang diadopsi oleh Indonesia dari Bank Dunia.Penelitian ini menggunakan metode pendekatan Yuridis Normatif, yang terdiri dari bahan hukum primer dan sekunder. Metode penelitian yang dipergunakan dalam penyusunan tesis ini adalah metode penelitian hukum yuridis normatif. Bentuk penelitian yang digunakan penulis ialah penelitian prespektif analisis. Teknik yang digunakan dalam mengumpulkan data adalah studi Pustaka dan Teknik analisis data yang digunakan penulis dalam penulisan ini ialah analisis kualitatif.Hasil dari penelitian ini, ialah dengan adanya implikasi pada kewajiban laporan keuangan ini memberikan beban kepada masyarakat dalam melaksanakan usaha mikro dan kecil. Pertama kewajiban laporan keuangan yang bertentangan dengan perspektif EODB, kedua kewajiban Laporan Keuangan tidak dapat menunjang Usaha Mikro dan Kecil, dan ketiga adanya Kewajiban Laporan Keuangan pada Perseroan Perorangan mengakibatkan kesulitan bagi masyarakat dalam melaksanakan usaha Mikro dan Kecil.Adapun akibat dari adanya laporan keuangan ialah sanksi admintratif berupa : a. teguran tertulis; b. penghentian irak akses atas layanan; atau c. perrcabutan status badan hukum.